FAKTOR-FAKTOR PENYEBAB KEMISKINAN KULTURALDAN MODEL PENGENTASAN BERBASIS KEARIFANLOKAL - Putu Ari Mulyani (Jurnal Ilmiah Satyagraha, 2020)
This study aims to determine the main factors leading causes of cultural povertyand developing poverty aleviation model based on local wisdom, such as Hindubased-philosophy TatTwam Asi (if I were you) in the community of Kintamani tourist area. The objectivesacomplishment of the study were carried out by using the paradigm prototypicalstudies, combined with reflective analysis method. It was found that the mainfactors causing poverty in certain parts of Kintamani community were culturalvalues that lead them difficult to reduce the poverty, such as the cultural habit ofbegging, laziness, pessimistic, easy to quit, lack of motivation, resigned to fatefamily situation that been poor hereditary, and low education level. Povertyalleviation model was proposed by elaborating Tat Twam Asi values in thecommunity of Kintamani tourist area through functionalization of social andculture institutions.